2015
DOI: 10.3109/00365513.2015.1066848
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of citalopram on plasma concentrations of thromboxane B2

Abstract: In this study we have shown that even short-term citalopram therapy led to a suppression of thromboxane B2 production in aspirin-treated patients. This suppressive effect correlates with actual plasma concentration of citalopram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…It may be tempting to interpret available indirect evidence to evaluate a potential interaction between SSRIs and ASA. However, in vitro data on established primary haemostasis/bleeding-related platelet markers and function parameters are disparate, many supporting the presence, [49][50][51][52][53] but some the absence, 54 of an SSRI + ASA bleeding interaction. In addition, apart from intracellular serotonin depletion, further mechanisms/molecular routes whereby SSRIs may affect the risk of bleeding have been discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be tempting to interpret available indirect evidence to evaluate a potential interaction between SSRIs and ASA. However, in vitro data on established primary haemostasis/bleeding-related platelet markers and function parameters are disparate, many supporting the presence, [49][50][51][52][53] but some the absence, 54 of an SSRI + ASA bleeding interaction. In addition, apart from intracellular serotonin depletion, further mechanisms/molecular routes whereby SSRIs may affect the risk of bleeding have been discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They include platelet aggregation 55 but also parameters outside of the platelet such as vascular tone and gastric acid secretion 56 . It has also been suggested that the platelet effect of concurrent SSRI and ASA treatment could be larger in individuals with ASA resistance 51 . Taken together, it appears difficult to determine from the complex body of indirect data whether concurrent use of an SSRI and ASA leads to sub‐additive, additive or synergistic effects regarding bleeding – in other words, whether an interaction exists or not.…”
Section: Discussionmentioning
confidence: 99%
“…Autoři uzavírají, že pokud jsou PPI užívány v kombinaci s escitalopramem, je nutno dávku redukovat na polovinu [38]. V našem souboru z geriatrického oddělení užívalo PPI inhibitory 70 % pacientů a koncentrace citalopramu se u nich pohybovaly vysoko nad terapeutickým rozmezím [39]. Podle analýzy údajů z geriatrické databáze v Bavorsku téměř 60 % pacientů užívalo aspoň 1 lék prodlužující QT interval, 2 nebo více léků prodlužujících QT interval užívalo 22 % geriatrických pacientů [40].…”
Section: Rizikové Faktory: Stáří Polymorbidita Polymedikaceunclassified